2019
DOI: 10.1103/physrevd.99.054027
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon and Δ isobar in a strong magnetic field

Abstract: We investigate the static properties of the nucleon in the presence of strong magnetic fields and discuss the consequent changes of the nucleon structure, based on the Skyrme model. The results show that at large values of the magnetic field (∼ 10 17 to 10 18 G), which is supposed to appear in heavy-ion collision experiments at RHIC energies, the soliton starts to deviate from the spherically symmetric form and its size starts to change. At extremely large values of the magnetic field (∼ 10 19 G), which may be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Considering the axial symmetry imposed by magnetic fields, we follow the ansatz in Ref. [8] to deform the spatial space as…”
Section: Formalismmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the axial symmetry imposed by magnetic fields, we follow the ansatz in Ref. [8] to deform the spatial space as…”
Section: Formalismmentioning
confidence: 99%
“…Many theoretical investigations based on the lattice QCD method or effective QCD theories, such as NJL models, have shown that strong magnetic fields can modify the quark potential and meson properties owing to complex QED-QCD interactions [5][6][7]. However, there are relatively few studies in regard to the modification of baryon properties in the presence of strong magnetic fields [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For another, since neutral pions are Nambu-Goldstone bosons of the chiral symmetry breaking, the modifications of their properties in an external magnetic field will help to understand the effects of magnetic fields on the chiral phase transition, and thus are extensively investigated recently . Furthermore, there are some other works involving heavy mesons [60][61][62][63][64][65][66][67][68][69][70][71] and baryons [72][73][74][75][76][77][78] in the magnetic field.…”
Section: Introductionmentioning
confidence: 99%